Gametophytic and sporophytic expression of anther-specific genes in developing tomato anthers. - Ursin, V M (1989)
The tissue localization of transcripts corresponding to five anther-specific cDNA clones isolated from tomato was determined. Transcripts specified by three of the cDNA clones were first detectable in anthers containing mitotic-stage gametophytes and were localized to the gametophyte. Transcripts specified by the two other cDNA clones were not detectable until anthers had reached a later developmental stage; these transcripts were also localized to the (now bicellular) gametophytes. Transcript levels for all of the cDNAs increased during gametogenesis and reached maximal levels in mature pollen grains. These mRNAs persisted in in vitro-grown pollen tubes, concentrating toward the tips of the growing tubes. At flower maturity, transcripts specified by each of the cDNAs were also detected in the epidermal and endothecial cell layers of the anther wall. The spatial distribution of transcripts in the anther wall was confined to that region of the anther that surrounds the locule. Transcripts were not detected in the sterile tip of the anther or in the filament. mRNA levels for these cDNA clones were markedly reduced in the anthers of several independent male-sterile mutants of tomato. Our results provide evidence that these anther-specific cDNAs represent genes expressed in both the gametophytic and sporophytic phases of the plant life cycle. The patterns of mRNA accumulation observed support the hypothesis that the proteins encoded by these genes function during pollen development and pollen tube growth.